Improving Discipline Character through Scouting Activities in Elementary Schools - Arif Setyawan; Wakhudin Wakhudin (UM Purwokerto Press, 2023)
Character education in scouting is believed to be able to change current problems, especially disciplinary problems This research was conducted considering the importance of student discipline character that has begun to decline, one way to improve the disciplinary character is through advanced activities. The purpose of this study is to analyze disciplinary character improvement activities carried out with scout activities along with their advantages and disadvantages. The research method used is a qualitative approach with a case study method, using data collection techniques in the form of interviews, observations and documentation studies. The data analysis technique used in this study is the Miles and Huberman interactive analysis model. From this research it can be concluded that scout activities can be used as a way to improve disciplinary character.